정보중심 마이크로서비스 기반 자율차량 연구 방향에 대한 제언 - 무하마드 아티프 우르 레흐만; 김병서; Rehman, Muhammad Atif Ur; Kim, Byung-Seo (The journal of the institute of internet, broadcasting and communication : JIIBC, 2021)
By changing the bulky monolithic services architecture to a microservices-based architecture, industries are managing the rising complexity of Autonomous Vehicles. However, the underlying communication mechanisms for the utilization and distribution of these microservices are incapable of fulfilling the requirements of the futuristic AV, because of the stringent latency requirements along with intermittent and short-lived connectivity issues. This paper proposes to tackle these challenges by employing the revolutionary information-centric networking (ICN) paradigm as an underlying communication architecture. This paper argues that a microservice approach to building autonomous vehicle systems should utilize ICN to achieve effective service utilization, efficient distribution, and uniform service discovery. This research claims that the vision of an information-centric microservices will help to focus on research that can fill in current communication gaps preventing more effective, and lightweight autonomous vehicle services and communication protocols. 사물인터넷과 자유주행 차량의 급속한 기술 발전과 함께, 그 시스템의 복잡성의 수준도 증가하고 있다. 따라서 관련 기업들은 기존의 부피가 큰 단일 서비스 아키텍처를 마이크로서비스 기반 아키텍처로 변경함으로써 증가하는 복잡성을 관리해오고 있다. 그러나 이러한 마이크로서비스의 활용과 배포를 위한 기본 통신 메커니즘은 간헐적이고 연결상태의 문제와 함께 짧은 지연 시간 요건 때문에 미래형 자율주행차량의 요건을 충족하기 어려웠다. 본 논문에서는 정보 중심 네트워킹(ICN) 패러다임을 기본 통신 아키텍처로 채택하여 기존의 문제점들을 해결할 것을 제안한다. 본 연구에서는 자율 차량 시스템을 구축하기 위한 마이크로서비스 접근방식이 ICN을 활용하여 좀 더 효과적인 서비스 제공 및 효율적인 서비스 분배와 균일한 서비스 발견을 달성할 수 있다는 부분에 대하여 조사, 분석 하였다. 본 논문에서 제시하는 방향성은 정보 중심의 마이크로서비스 접근 방식의 비전이 더 효과적이고 가벼운 자율 차량 서비스와 통신 프로토콜 연구에 초점을 맞추는 데 도움이 될 것이다.